Significance of PD-L1 expression in pulmonary metastases from head and neck squamous cell carcinoma. (June 2018) - Okada, Satoru; Itoh, Kyoko; Ishihara, Shunta; Shimada, Junichi; Kato, Daishiro; Tsunezuka, Hiroaki; Miyata, Naoko; Hirano, Shigeru; Teramukai, Satoshi; Inoue, Masayoshi
Abstract: Background: The mechanism by which tumors escape the immune system has been actively investigated and is partly explained by the programmed death-1 (PD-1) and its ligand (PD-L1) pathway. This study is aimed at clarifying the prognostic significance of PD-L1 expression in patients with surgically resected pulmonary metastases of head and neck squamous cell carcinoma (HNSCC). Patients and methods: A retrospective review was conducted of 26 HNSCC patients who underwent complete resection of pulmonary metastases. PD-L1 expression in both the primary and metastatic tumors was evaluated using immunohistochemistry (anti-PD-L1 antibody, clone SP263). High PD-L1 expression was defined as ≥50% of tumor cells with positive staining. Survival and prognostic impacts following pulmonary metastasectomy were analyzed based on the PD-L1 expression level. Results: The patients included 23 men and 3 women, with a median age of 65 years. Six (23%) of the pulmonary metastatic cases showed high PD-L1 expression, while their corresponding primary lesions had low PD-L1 expression. The 5-year overall survival rate after pulmonary metastasectomy was 57.6% in all cases. The 5-year overall survival rates were 72.5% and 16.7% in the low and high PD-L1 groups, respectively ( p < 0.001). Multivariate analysis demonstrated that high PD-L1 expression and older age (>65 years) correlated independently with a shorter overall survival ( p < 0.001). Conclusions: High PD-L1 expression in pulmonary metastases could be an independent predictor of poor outcome in HNSCC patients undergoing pulmonary metastasectomy. This is the first report evaluating the prognostic implication of PD-L1 expression in metastatic HNSCC. Highlights: PD-L1 expression in surgically resected pulmonary metastases of HNSCC was analyzed. High PD-L1 expression (≥50%) was found in 23% of cases. PD-L1 expression was inconsistent between primary tumor and pulmonary metastases. High PD-L1 expression in pulmonary metastases of HNSCC was a poor prognostic factor.